Effect Of Debt-To-Asset And Return On Equity Ratio On Going Concern Opinions - Aviva, Itsla Yunisva; Suriyani, Elma; Himawan, Hilmi Satria; Hafizi, Muhammad Riza (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2025)
This study aims to analyze the effect of the debt-to-asset ratio (DAR) and return on equity (ROE) on the issuance of going concern audit opinions, both partially and simultaneously. The study adopts a quantitative approach with a causal-comparative design. The research sample consists of 11 energy sector companies listed on the Indonesia Stock Exchange from 2013 to 2022, selected through purposive sampling from a population of 82 companies. Data were analyzed using binary logistic regression with the help of Eviews 12 software. The results show that DAR has a positive and significant partial effect on going concern audit opinion, indicating that higher debt levels increase the likelihood of receiving such an opinion. In contrast, ROE has no significant partial effect, suggesting that profitability does not significantly influence auditors' judgments regarding going concern in this sector. However, DAR and ROE jointly (simultaneously) have a significant positive effect on going concern audit opinions, implying the importance of evaluating financial risk and performance collectively. The model’s McFadden R-square value is 21.7%, indicating a moderate explanatory power where the variables studied account for about one-fifth of the variation in going concern audit opinion issuance. The remaining 78.3% is influenced by other factors not included in the model. This study contributes to the auditing literature by focusing specifically on the underexplored energy sector in Indonesia and provides insights into how financial risk indicators can inform auditors’ assessments. The findings emphasize the need for auditors and stakeholders to consider a broader range of financial indicators in evaluating a firm's going concern status